EFEITO DA SUPLEMENTAÇÃO MINERAL SOBRE O CRESCIMENTO E DESENVOLVIMENTO DE BEZERROS DA RAÇA NELORE - AMORIM, Lidianny dos Santos,; PALERMO, Suyane Barros Chimene,; GONÇALVES, Isabela Pinto,; ARRUDA, Rosana Moreira da Silva,; FERRAZ, André Luiz Julien,; OLIVEIRA, Dalton Mendes, (ANAIS DO ENIC, 2023)
-